2019
DOI: 10.1590/1807-3107bor-2019.vol33.0042
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity and biocompatibility of a new bioceramic endodontic sealer containing calcium hydroxide

Abstract: This study evaluated the cytotoxicity and biocompatibility of a new bioceramic endodontic sealer (i.e., Sealer Plus BC) in comparison with those of MTA Fillapex and AH Plus. L929 fibroblasts were cultured and Alamar Blue was used to evaluate cell viability of diluted extracts (1:50, 1:100, and 1:200) from each sealer at 24 h. Polyethylene tubes that were filled with material or empty (as a control) were implanted in the subcutaneous tissue of rats. The rats were killed after 7 and 30 d (n = 8), and the tubes w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
59
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(73 citation statements)
references
References 39 publications
(67 reference statements)
3
59
0
1
Order By: Relevance
“…The implantation of biomaterials within the subcutaneous connective tissue of rats has been widely accepted as an essential test to access the biocompatibility of biomaterials in various specialties. 17,[21][22][23][24] In conjunction with previous reports, [13][14][15]18,25 the results of the present study have shown that the histological response could be used as a preliminary source of information on biocompatibility.…”
Section: Discussionsupporting
confidence: 74%
“…The implantation of biomaterials within the subcutaneous connective tissue of rats has been widely accepted as an essential test to access the biocompatibility of biomaterials in various specialties. 17,[21][22][23][24] In conjunction with previous reports, [13][14][15]18,25 the results of the present study have shown that the histological response could be used as a preliminary source of information on biocompatibility.…”
Section: Discussionsupporting
confidence: 74%
“…MTA Fillapex (Angelus, Brazil) is a salicylate resin bioceramic sealer, with enhanced physical properties but has been shown to be relatively cytotoxic and genotoxic [15], [19], [20].…”
Section: Introductionmentioning
confidence: 99%
“…There is a substantial correlation between the development of the fibrous capsule and material biocompatibility, as it is considered the immune response rendering foreign bodies well tolerated by the tissues [20], [25], [36].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the new calcium silicate-based Sealer Plus BC (MK Life, Porto Alegre, RS, Brazil) and Bio-C Sealer (Angelus, Londrina, PR, Brazil) were introduced into the market. Sealer Plus BC and Bio-C Sealer are biocompatible and have appropriate setting time, flow, and radiopacity, besides alkalinization capacity [15][16][17][18]. Although the solubility of these sealers is higher than the rates required by ISO 6876 standard, both materials showed a decrease in solubility when immersed in phosphate-buffered saline (PBS), in addition to a low volumetric change after immersion in distilled water or PBS [17][18][19].…”
Section: Introductionmentioning
confidence: 99%